2021
DOI: 10.2196/28168
|View full text |Cite
|
Sign up to set email alerts
|

New Evidence in the Booming Field of Online Mindfulness: An Updated Meta-analysis of Randomized Controlled Trials

Abstract: Background There is a need to regularly update the evidence base on the effectiveness of online mindfulness-based interventions (MBIs), especially considering how fast this field is growing and developing. Objective This study presents an updated meta-analysis of randomized controlled trials assessing the effects of online MBIs on mental health and the potential moderators of these effects. Methods We conduc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(73 citation statements)
references
References 154 publications
5
65
3
Order By: Relevance
“…Meta-analyses of posttreatment effects were conducted for all 3 comparisons, and meta-analyses of follow-up effects were conducted for the nonclinician-guided intervention versus unguided intervention and nonclinician-guided intervention versus control comparisons. Although both posttreatment standardized mean difference (SMD) and pretest-posttest control group ( d ppc2 ) [ 37 ] effect sizes have been utilized in similar meta-analyses [ 38 , 39 ], we determined that the posttreatment SMD effect size was most appropriate due to the lack of pre-post correlation values available from the included studies and the criticisms of pre-post effect size methods [ 40 ]. A sensitivity analysis was conducted comparing the 2 methods and resulted in the same pattern of findings.…”
Section: Methodsmentioning
confidence: 99%
“…Meta-analyses of posttreatment effects were conducted for all 3 comparisons, and meta-analyses of follow-up effects were conducted for the nonclinician-guided intervention versus unguided intervention and nonclinician-guided intervention versus control comparisons. Although both posttreatment standardized mean difference (SMD) and pretest-posttest control group ( d ppc2 ) [ 37 ] effect sizes have been utilized in similar meta-analyses [ 38 , 39 ], we determined that the posttreatment SMD effect size was most appropriate due to the lack of pre-post correlation values available from the included studies and the criticisms of pre-post effect size methods [ 40 ]. A sensitivity analysis was conducted comparing the 2 methods and resulted in the same pattern of findings.…”
Section: Methodsmentioning
confidence: 99%
“…This potential hypothesis is supported by the recent review of Borghouts [ 31 ], which points toward a generally higher engagement for guided (vs unguided) interventions and to the importance of social connectedness as a facilitator of user engagement. In addition, a recent meta-analysis [ 32 ] focusing specifically on web-based mindfulness found that web-based MBIs resulted in higher effect sizes for stress when offered guidance. As there was also no personal contact between the research team and the respondents, one could say that our study results may be similar to what one might expect to find in a real-world user situation, where despite high levels of app download, only a small portion of users actually use the apps for a longer period [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“… 14 Furthermore, virtual delivery of MBM through meditation/well-being mobile applications and online interventions holds new promise for equitable access and delivery. 28 , 29 …”
Section: A Snapshot Of Current Evidence and Guidelines For Mbm In Can...mentioning
confidence: 99%